Usefulness and applications of entropy measurement / Muhamad Arif Hashim and Roshidi Din - Hashim, Muhamad Arif; Din, Rashidi (2004)
Basically, entropy is a measure of uncertainty, a mathematical equation in defining the between certainty and uncertainty. Although the term has been around the world for a long time, there still lack in literature for better understanding of its usefulness and applications. In this paper, we mainly focus on the entropy by clarifying the real meaning of it in a simple and understandable mathematical way from a communication field point of view. The entropy properties and rules will be discussed in detail and we try to relate it with logarithm measure for a better understanding of entropy scenario. Some usefulness and applications of entropy in various fields such as communication, thermodynamic will be presented. We conclude this paper and state some challenges in applying entropy measurement. Hopefully, it will bring a new and better understanding of entropy not just to researcher and mathematician, but also to other related individual such as engineer and academician in applying this powerful measurement tool in their field.